2010
DOI: 10.1016/j.bbabio.2010.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and disease converge in the mitochondrion

Abstract: Mitochondrial DNA (mtDNA) mutations are long known to cause diseases but also underlie tremendous population divergence in humans. It was assumed that the two types of mutations differ in one major trait: functionality. However, evidence from disease association studies, cell culture and animal models support the functionality of common mtDNA genetic variants, leading to the hypothesis that disease-causing mutations and mtDNA genetic variants share considerable common features. Here we provide evidence showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 95 publications
0
20
0
Order By: Relevance
“…A focus on mitonuclear coadaptation is likely to contribute tangibly to our understanding of basic ecological concepts, such as speciation and the dynamics of sexual conflict (Hill, ; Wolff et al ., ). Furthermore, the implications of such interactions might resonate beyond the evolutionary and ecological sciences, into the realm of biomedicine (Mishmar & Zhidkov, ; Wallace, ; Dowling, ; Gershoni et al ., ). To inform future research directions, we identify and discuss five themes that have emerged from the study of mitonuclear interactions over the past two decades (Table ).…”
Section: Evidence For Coevolution Of Mitochondrial and Nuclear Genomesmentioning
confidence: 99%
“…A focus on mitonuclear coadaptation is likely to contribute tangibly to our understanding of basic ecological concepts, such as speciation and the dynamics of sexual conflict (Hill, ; Wolff et al ., ). Furthermore, the implications of such interactions might resonate beyond the evolutionary and ecological sciences, into the realm of biomedicine (Mishmar & Zhidkov, ; Wallace, ; Dowling, ; Gershoni et al ., ). To inform future research directions, we identify and discuss five themes that have emerged from the study of mitonuclear interactions over the past two decades (Table ).…”
Section: Evidence For Coevolution Of Mitochondrial and Nuclear Genomesmentioning
confidence: 99%
“…8 Accordingly, elevated amino acid replacement rates indicating positive selection have been identified in nDNA-encoded subunits that closely interact with fast-evolving mtDNAencoded subunits within OXPHOS complexes with experimentally determined three-dimensional structure, namely complex III, complex IV, and part of complex V. [9][10][11][12] In a recent rigorous sequence analysis, we identified three complex I nDNAencoded subunits that underwent accelerated amino acid replacement during the course of primate evolution and are thus likely candidates to interact with the fast-evolving mtDNA-encoded subunits. 13 Since cytonuclear subunit interactions play important roles in disease and evolution, 14,15 we sought to decipher such direct interactions within complex I. Here, we applied combined evolutionary and experimental approaches to analyze the interaction of the fast-evolving nDNAencoded subunits NDUFC2 and NDUFA1 with the mtDNA-encoded subunits of complex I.…”
Section: Introductionmentioning
confidence: 99%
“…However, accumulating evidence suggests that many common variants in the mitochondrial and nuclear genomes have functional impacts [3]. Specifically, ancient mitochondrial DNA (mtDNA) variants and genetic backgrounds (haplotypes, haplogroups) have been associated with an altered tendency to develop a variety of complex traits [3–5] that affected mitochondrial activity in cell culture experiments [6–9] and which conferred adaptive advantages over the course of human evolution [10–12]. Whereas it has been shown that mtDNA variants affected mitochondrial protein activities, such as oxidative phosphorylation (OXPHOS) or the production of reactive oxygen species (ROS), the impact of mtDNA variants on the regulation of gene expression has drawn little attention.…”
Section: Introductionmentioning
confidence: 99%